2017
DOI: 10.1007/s10493-017-0144-8
|View full text |Cite
|
Sign up to set email alerts
|

Deltamethrin as inductor agent of precocious ovarian degeneration in Rhipicephalus sanguineus s.l. (Acari: Ixodidae) ticks

Abstract: The cosmopolitan species Rhipicephalus sanguineus s.l. is one of the most widely distributed ticks all over the world. These ectoparasites are vectors of several pathogens and cause significant direct damage to their hosts. The biological success of these ectoparasites has been attributed to their ovaries and salivary glands, organs that ensure their survival in various environmental conditions. The importance of the ovaries in ticks is that, after mating, the individuals are able to lay approximately three th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Our results correspond with the investigations carried out by other authors (Friesen and Kaufman 2003;Oliveira et al 2008;Roma et al 2010;Camargo-Mathias et al 2017), who demonstrated cytotoxic effects of pyrethroids on the tick reproductive system. Cypermethrin inhibited oocyte development in Amblyomma hebraeum Koch (Friesen and Kaufman 2003).…”
Section: Discussionsupporting
confidence: 93%
“…Our results correspond with the investigations carried out by other authors (Friesen and Kaufman 2003;Oliveira et al 2008;Roma et al 2010;Camargo-Mathias et al 2017), who demonstrated cytotoxic effects of pyrethroids on the tick reproductive system. Cypermethrin inhibited oocyte development in Amblyomma hebraeum Koch (Friesen and Kaufman 2003).…”
Section: Discussionsupporting
confidence: 93%
“…Oocytes were deformed with the break in the nucleus region. The abnormal morphological and structural changes observed in the present study were previously reported in the ovaries of the ticks treated with other phytoacaricides [ 21 , 29 ] and synthetic acaricides like deltamethrin, amitraz [ 38 , 39 , 40 ], fipronil [ 33 , 34 ], permethrin [ 36 , 37 ] and cypermethrin [ 74 ]. The above studies indicated the inhibitory effect of these acaricides on the oocytes at different stages of their development.…”
Section: Resultssupporting
confidence: 83%
“…In addition to their direct acaricidal activity due to neurotoxicity, many herbal extracts produced accelerated degeneration of salivary glandular tissue and changes in the morphophysiology of reproductive organs in ticks [ 19 , 20 ]. The histopathological and ultrastructural alterations induced by phytoacaricides [ 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] were comparable to those induced by conventional synthetic chemical acaricides [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 91%
“…is the application of synthetic chemical acaricides. Among these are fipronil, able to cause alterations in the reproductive system and salivary glands (Oliveira et al ., 2007, 2009; Pereira et al ., 2009, 2011); permethrin, which causes degeneration of the synganglion and alterations in the salivary glands and reproductive system (Nodari et al ., 2011, 2012a; Roma et al ., 2011, 2013, 2014); fluazuron, which acts on the integument and midgut (Oliveira et al ., 2012, 2013, 2014); dinotefuran, which acts on the reproductive system of females (Oliveira et al ., 2016, 2017); and deltamethrin, which affects the synganglion and the reproductive system of females (Camargo‐Mathias et al ., 2017; Pereira et al ., 2017). Despite their efficacy, the indiscriminate application of acaricides has several disadvantages, including toxicity to non‐target organisms and environmental contamination (Camargo‐Mathias, 2013, 2018).…”
Section: Introductionmentioning
confidence: 99%